Sintesis Pasangan Asam-Basa Polianilin/Polianilin Tersulfonasi (PANI/SPAN) sebagai Material Hole-Injection Layer pada Perangkat Optoelektronik Organik - Rizqka Humaidi, Aldini
One of the most developed applications of conductive polymer is being a predominant material for Hole-Injection Layer (HIL) in organic optoelectronic devices. Poly(3,4-ethylenedioxythiophene)-polystyrenesulfonate (PEDOT-PSS) has been the most frequent polymer used for this application up to now due to its high conductivity and transparency, well-defined work-function, as well as its extremely good proccessability. Polyaniline (PANI) then rises up with its promising potency as a more economic conductive polymer compared to PEDOT-PSS. However, PANI is hard to process; this triggers scientists around the world to apply some modifications towards the structure by adding polar functional groups. The most intriguing form among those modifications is sulfonated polyaniline (SPAN), in which a sulfonate (–SO3-) group is attached to the ring. Despite its high solubility in water and its ability to conduct an ohmic contact with metals, SPAN is very hygroscopic and is not soluble in common organic solvent. In this research we have synthesized a polymer blend of PANI/SPAN and have investigated optimum chlorosulfonic acid concentration to synthesize the “template SPAN” beforehand. A mixture of 20% v/v of chlorosulfonic acid in chloroform as sulfonating agent yielded the optimum SPAN among the other concentrations. The result of the blending process was a green powder of PANI/SPAN which is soluble in water, methanol, ethanol, and basic solution. IR spectra of PANI/SPAN quite resembles one of PANI, yet two specific peaks at 1023 and 1070 cm-1 which represent the vibration of aryl–S linkage emerge, similar to SPAN spectra. Raman spectra reconfirms the same vibration at 1213 cm-1. Peak comparisons of PANI, SPAN, and PANI/SPAN at both 572 and 420 cm-1 verify interactions that take place between PANI and SPAN chain. Frequency response of conductivity (?(?)) affirms the characteristic of PANI/SPAN was PANI-like (metallic) but there is also a hint of SPAN-like (semiconductor) character in low frequencies. Conductivity of PANI, SPAN, and PANI/SPAN in 30 Hz are 0,1757; 0,0010; and 0,0132 S cm-1, respectively. It is then concluded that a polymer blend made of PANI and SPAN with different characteristic has been successfully synthesized.